Impact of biosynthesized silver nanoparticles cytotoxicity on dental pulp of albino rats (histological and immunohistochemical study) - Mervat M. Youssef; Merhan N. El-Mansy; Ola M. El-Borady; Enas M. Hegazy (Elsevier, 2021)
This study aimed to evaluate the potential cytotoxic effect of oral administration of silver nanoparticles (Ag-NPs) on adult albino rats' pulp tissue; due to the enormous uses of Ag-NPs in the medical and dental field. The Ag-NPs were synthesized via the green process using peels of pomegranate extract. The pomegranate-mediated Ag-NPs were subjected to morphological and spectral analysis through ultraviolet visible absorption spectra, transmission electron microscopy, Fourier transforms infrared, Zeta-potential measurements, and energy dispersive X-ray spectroscopy. The structural and morphological characterization techniques confirmed the proper synthesis of biosynthesized Ag-NPs with a size around 20 ​nm and the surface plasmon resonance peak within 400-450 ​nm. The oral cytotoxic effect of Ag-NPs was assessed through detecting the histological (hematoxylin & eosin, Masson's trichrome) and immunohistochemical (vascular endothelial growth factor (VEGF), Caspase-3 proteins) variations. The data was analyzed statistically through using the SPSS software. Dental pulp tissues of albino rats-treated with Ag-NPs revealed that most of the odontoblasts with marked hydropic degeneration, vacuolization of their cytoplasm, loss of organization and apoptosis. Marked vasodilatation and cognition of blood vessels were detected. There was weak to moderate positive reactivity to Masson's trichrome stain. There was statistically significant decrease in the expression of VEGF in the treated group and highly statistically significant increase in the expression of Caspase-3 in comparison with the control group. Conclusion: Oral administration of Ag-NPs induced size and dose-dependent structural changes in the pulp tissue of adult male albino rats.